Ethical canons of organ transplantation from Islamic perspective: a brief review - Hashi, Abdurezak Abdulahi (Revelation and Science, IIUM, 2015)
Organ transplantation involves removing a given body organ from prospective organ donor, dead or alive, and transplanting it into the body of an intended recipient, often with the aim of replacing the recipient’s damaged or failing organ with a healthy one. Apart from the concerns made about the possible health complications that might arise from conducting this operation, this practice raises certain moral and legal issues related to the dignity and sanctity of the bodies of those involved. This paper uses analytical method, and intends to expose the ethical and jurisprudential canons that regulate organ transplantation from Islamic perspective. With brief introduction to organ transplantation, this paper presents a concise review of the opinions of the Muslim jurists and ethicists on this subject.